Correlation between Diabetes Mellitus Onset with Diabetic Nephropathy Caseof the In-Patients Treated in RS Muhammadiyah Ahmad Dahlan Kediri - Kusuma, Satria Candra; AG, Muhammad Masykur (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2019)
The average numberof diabetes mellitus patients who underwenthospitalization inRS Muhammadiyah Ahmad Dahlan Kedirireached 11.6% per month. The age rage of the patients was between 5-15 years. They usually suffered from complications such as DM nephropathy, hypertension and hyperglycemia, that this fact should be inspectedfurther. This study was intended to cover as to how significant is the correlation between diabetes mellitus onset and the caseof diabetic nephropathy suffered by patients. The design of this study was cross sectional correlative descriptive. The sample of this study was the DM in-patients with the complication of diabetic nephropathy taken using total sampling. Spearman Rank was used as the data analysis technique. This study has found that 49 (84.48%) out of 58 diabetes mellitus patients were suffered from diabetic nephropathy too. Meanwhile, according to the result of hypothesis test, the r-count value was 0.743 and the significance rate was 0.000, which mean that there was a relation between the variable of diabetes mellitus onset and variable of diabetic nephropathy case occurred to the in-patients of RS Muhammadiyah Ahmad Dahlan Kediri.